Revitalisasi limbah tekstil: Pengembangan serat komposit berkelanjutan dari baju bekas - Putra, Arya Rahmadi; Karim, Farhan Sajidan; Hamid, Muhammad Akram (Jurnal Teknologi Cerdas, 2024)
In the era of globalization and the rapid growth of the fashion industry, significant environmental sustainability challenges arise due to textile waste accumulation. This manuscript proposes an innovative concept for the revitalization of textile waste through the development of sustainable composite fibers from used clothing. Utilizing theoretical approaches and literature analysis, this paper explores the potential of textile waste as a raw material source for creating composite fibers, which, until present, predominantly rely on limited natural resources. The discussion in this paper encompasses several aspects, including the process of selecting and transforming used clothing into fibers, the development of composite materials, and the potential applications of the resulting sustainable products. Additionally, an examination of the economic, environmental, and social aspects of this initiative demonstrates that the revitalization of textile waste offers a holistic solution not only in mitigating environmental impacts but also in promoting a circular economy and product innovation. The main conclusions drawn underscore the benefits of this approach and call upon stakeholders in the textile industry to view waste as a resource, aligning with global efforts towards a more sustainable future.